Reflection, Memory, and the Fine Art of Poetry: Reading Memories of Words by Jaydeep Sarangi - Sreetanwi Chakraborty (Litinfinite, 2023)
In Fundamentals of the Art of Poetry, Oscar Mandel opines: “The work of art is that special form among all the forms created by man for which there is one and only one criterion of success- namely the satisfaction it delivers.” (Mandel 24) It is through this deft work of art that gives birth to Jaydeep Sarangi’s poetic peregrination. Memories of Words, as his book is titled, is a fine balance of nostalgia, tranquility, memory, and the art of poetic perfection. Memory intertwines with imagery in his poems and gives birth to ‘feathers and flute’.